Neuroprotective effect of acute ethanol intoxication in TBI is associated to the hierarchical modulation of early transcriptional responses - Chandrasekar, Akila; Aksan, Bahar; Mauceri, Daniela (Experimental neurology, 2018)
Ethanol intoxication is a risk factor for traumatic brain injury (TBI) but clinical evidence suggests that it may actually improve the prognosis of intoxicated TBI patients. We have employed a closed, weight-drop TBI model of different severity (2cm or 3cm falling height), preceded (−30min) or followed (+20min) by ethanol administration (5g/Kg). This protocol allows us to study the interaction of binge ethanol intoxication in TBI, monitoring behavioral changes, histological responses and the transcriptional regulation of a series of activity-regulated genes (immediate early genes, IEGs). We demonstrate that ethanol pretreatment before moderate TBI (2cm) significantly reduces neurological impairment and accelerates recovery. In addition, better preservation of neuronal numbers and cFos+cells was observed 7days after TBI. At transcriptional level, ethanol reduced the upregulation of a subset of IEGs encoding for transcription factors such as Atf3, c-Fos, FosB, Egr1, Egr3 and Npas4 but did not affect the upregulation of others (e.g. Gadd45b and Gadd45c). While a subset of IEGs encoding for effector proteins (such as Bdnf, InhbA and Dusp5) were downregulated by ethanol, others (such as Il-6) were unaffected. Notably, the majority of genes were sensitive to ethanol only when administered before TBI and not afterwards (the exceptions being c-Fos, Egr1 and Dusp5). Furthermore, while severe TBI (3cm) induced a qualitatively similar (but quantitatively larger) transcriptional response to moderate TBI, it was no longer sensitive to ethanol pretreatment. Thus, we have shown that a subset of the TBI-induced transcriptional responses were sensitive to ethanol intoxication at the instance of trauma (ultimately resulting in beneficial outcomes) and that the effect of ethanol was restricted to a certain time window (pre TBI treatment) and to TBI severity (moderate). This information could be critical for the translational value of ethanol in TBI and for the design of clinical studies aimed at disentangling the role of ethanol intoxication in TBI.
Available online 4 January 2018
Gesehen am 09.04.2019